Increased Response Time and Triage Accuracy with Resetting of Systems and Spatial in a Hospital Emergency Room - Hapsari, Riandiani Dwi (Fakultas Kedokteran Universitas Brawijaya, 2021)
The triage system in the emergency room is crucial for categorizing patients based on the level of emergency and finding out further medical services for the patients. An accurate triage system will accelerate the IGD response time and result in better ER quality. The purpose of this study was to determine the factors influencing the accuracy of the triage location in the Emergency Room of a type C hospital as well as the relationship between the activation of the triage area and the emergency response time. The sample consisted of 30 patients before and 30 patients after the activation of the triage area. According to the priority level, the sample was then divided into ten patients each. This research used field experimental design with a Participatory Action Research approach. The results showed that the accuracy of the triage implementation in the Emergency Room of this hospital was influenced by the facilities and infrastructure, human resources, and the flow of patients in the emergency room. Based on the Wilcoxon test, there is an increase in P1 and P3 patient response time before and after triage activation but not significant. The increase in response time in P2 patients before and after the activation of the triage area is significant with p-value <0.046. This study concludes that the right triage system can increase emergency response time.